Restoration of Glycemic Control in Patients with Type 2 Diabetes Following Bariatric Surgery is Associated with Reduction in Microparticles - Cheng, V. (2011)
BACKGROUND: Microparticles bud from cellular elements during inflammation and are associated with vascular dysfunction related to type 2 diabetes. Although weight loss is known to reduce inflammation, the metabolic effects of bariatric surgery on microparticle concentration and composition are not known. OBJECTIVES: To determine the effect of bariatric surgery on microparticle concentration and correlate these changes with clinical parameters. SETTING: Multispecialty group practice METHODS: We studied 14 obese subjects with type 2 diabetes two weeks before and at one and 12 months following bariatric surgery. Nine of the patients underwent Roux-en-Y gastric bypass and 5 received gastric restrictive surgery. RESULTS: One month following surgery, body mass index was reduced by ~10%, glycemic control improved dramatically (P < 0.01), and there was a >60% reduction in endothelial, platelet microparticles and CRP levels (P < 0.05). Tissue factor microparticles reduced by 40% ( p = 0.1). Twelve months following surgery, BMI was reduced by ~20%, glycemic control was maintained (P < 0.01), and there was a >50% reduction in monocyte microparticles compared to pre-surgery. The reduction in monocyte microparticles one month after surgery was strongly associated with the reduction in hemoglobin A1c (P < 0.05). The reduction in monocyte microparticles 12 months following surgery correlated strongly with the reduction in body mass index (P < 0.05). CONCLUSION: The reduction in microparticles after bariatric surgery in patients with type 2 diabetes reflects an attenuation of inflammation and this mechanism may contribute to normalization of glycemic control.